Liquid phase assisted grain growth in Cu2ZnSnS4 nanoparticle thin films by alkali element incorporation. Issue 13 (14th February 2018) - Engberg, Sara; Canulescu, Stela; Schou, Jørgen
Abstract : We present a route where organic ligand-free, KCl-functionalized Cu2 ZnSnS4 nanoparticles grow into large, dense grains during annealing in nitrogen/sulfur atmosphere. Abstract : The effect of adding LiCl, NaCl, and KCl to Cu2 ZnSnS4 (CZTS) nanoparticle thin-film samples annealed in a nitrogen and sulfur atmosphere is reported. We demonstrate that the organic ligand-free nanoparticles previously developed can be used to produce an absorber layer of high quality. The films were Zn-rich and Cu-poor, and no secondary phases except ZnS could be detected within the detection limit of the characterization tools used. Potassium was the most effective alkali metal to enhance grain growth, and resulted in films with a high photoluminescence signal and an optical band gap of 1.43 eV. The alkali metals were introduced in the form of chloride salts, and a significant amount of Cl was detected in the final films, but could be removed in a quick water rinse.